2004
DOI: 10.1136/bjo.2003.037499
|View full text |Cite
|
Sign up to set email alerts
|

Refraction and keratometry in 40 week old premature (corrected age) and term infants

Abstract: Aim: To compare refraction and keratometry readings between premature and term babies at 40 weeks' postconceptional age (PCA), and the possible effect of birth weight (BW) and gestational age (GA) on ocular parameters. Methods: 33 preterm babies hospitalised in the neonatal unit between January and March 2002 were matched with 33 term babies born within the same period and hospitalised in the same unit. The preterm group underwent funduscopy at 4-5 weeks after delivery. Ophthalmic examination at 40 weeks' PCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
3
40
2
Order By: Relevance
“…7,24,25 In children with ROP, shallower anterior chambers, steeper corneal curvatures, and shorter axial lengths were shown to be related to gestational age and birth weight. 7,11,12,24,25 In our study, as expected, we found no relationships between gestational age and any of the studied anterior segment parameters. Because our study subjects had gestational ages >37 weeks and intrauterine eye growth had nearly completed after 37th week of gestation, the range of gestational ages may not have been sufficient to reveal significant relationships between gestational age and anterior segment structures.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…7,24,25 In children with ROP, shallower anterior chambers, steeper corneal curvatures, and shorter axial lengths were shown to be related to gestational age and birth weight. 7,11,12,24,25 In our study, as expected, we found no relationships between gestational age and any of the studied anterior segment parameters. Because our study subjects had gestational ages >37 weeks and intrauterine eye growth had nearly completed after 37th week of gestation, the range of gestational ages may not have been sufficient to reveal significant relationships between gestational age and anterior segment structures.…”
Section: Discussionsupporting
confidence: 62%
“…Our study population comprised preschool children, born at term, with birth weight of >2500 g. Previous studies had reported that prematurity and low birth weight have significant effects on the anterior segment, particularly in premature infants with/without ROP (Retinopathy of Prematurity). 7,11,12,24,25 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They eye always tends to emetropia (with no refractive errors) and, in order to compensate for the smaller APD at birth the cornea has a high power of refraction (47.6 diopters), which reduces progressively as the eye grows, reaching 42.5 diopters in adulthood. 1,2 Children born to full term have a slight tendency to hypermetropia. Population studies show that this hypermetropia tends to increase until 7 years of age and then there is a tendency to myopization until adulthood.…”
Section: Growth Of the Eye And Refractive Errorsmentioning
confidence: 99%